Utilization of residual liquid orange from juice processing as cultivation medium of Penicillium citrinum: Biological depuration of the residue and enzyme production. - Tavares, V. B.; Sivieri, K.; Ceron, C. R.; Silva, R. da; Trabuco, E.; Lombardi, F. R.; Gomes, E. (Soc Brasileira Quimica, 1998)
Penicillium citrinum grown in orange juice processing wastes medium under continuous agitation was studied in order to establish optimal conditions (incubation period, incubation temperature, initial pH and nitrogen addition) for biomass and ribonuclease production, as well as, biological depuration pf the wastes. Nitrogen addition to wastes medium increased the biomass and ribonuclease production and provides COD reduction. The soy meal shows to be the best nitrogen source. The conditions for a more favorable enzyme and biomass production and COD reduction were initial pH 6.0 and temperature of 27 degrees C, The maximum value obtained for these parameters on optimal conditions of cultivation was 11 U/mL of enzyme, 4 mg/mL of biomass (dry matter) and 55% of COD reduction, in 96 hours of incubation.
Keywords: wastes; fungal grown; COD